Estudo e implementação de um conversor cc-cc boost entrelaçado para um sistema de geração fotovoltaico conectado à rede - Moisés Martins Gonçalves (2020)
In recent years there has been a significant increase in the implementation of distributed generation, where it is possible to highlight the photovoltaic (PV) systems. One of the key points in the implementation of these systems is the extraction of maximum power from the PV panels. In this sense, two tools are essential for small systems: the CC-CC converter and the implementation of the maximum power tracking algorithm (MPPT), which have a great influence on the efficiency of the conversion process. The present work carries out the study and implementation of the interleaved boost converter (iBC), proposing a generalized modeling of small-signals for N-cells. In addition, it evaluates an MPPT algorithm using the current as a tracking variable, discussing the effects of the MPPT step and the time to update the variables on the efficiency of the algorithm, where it is validated experimentally in a 5,1 (kW) system.